Sistem Monitoring dan Controlling Kualitas Air Serta Pemberian Pakan Pada Budidaya Ikan Lele Menggunakan Metode Fuzzy, NodeMCU dan Telegram - Rizky Maulana; Kusnadi Kusnadi; Marsani Asfi (ITEJ (Information Technology Engineering Journals), 2021)
Catfish farming is one of the fields of business that is still popular today. Cultivation of catfish is a business solution that can be done by anyone. An important factor in the success of catfish farming is to maintain the quality of the pond water in order to keep it good and to provide feed that is carried out regularly. Each type of fish has different characteristics to pond water conditions. In the cultivation of catfish in tarpaulins, the air temperature must be maintained at 20-32 oC, then the pH of the air is good for catfish between 5.5-7.5. If the temperature and pH conditions are outside the specified values, the farmer must replace the fish pond water. Internet of Things (IoT) is a concept where devices can be connected and exchange data with each other through the internet network. In this study, the application of the Internet of Thing (IoT) There are several components used including NodeMCU, pH Sensor, Temperature Sensor, Ultrasonic Sensor, Relay, Pump, Servo Motor and Telegram Bot used for the interface. The fuzzy method used to measure water quality in catfish tarpaulin ponds is based on pH and temperature. The output of this research is a pump control that functions to replace or fill pool water.